2017
DOI: 10.1038/s41539-017-0004-7
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing a lexical legacy: reading experience is critical for the development of word reading skill

Abstract: OPENNurturing a lexical legacy: reading experience is critical for the development of word reading skill Kate Nation 1The scientific study of reading has taught us much about the beginnings of reading in childhood, with clear evidence that the gateway to reading opens when children are able to decode, or 'sound out' written words. Similarly, there is a large evidence base charting the cognitive processes that characterise skilled word recognition in adults. Less understood is how children develop word reading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 50 publications
10
76
0
1
Order By: Relevance
“…Some studies of L2 learning have found higher levels of vocabulary acquisition from more extensive reading (M. Horst, ; Webb & Chang, ) than usually reported in studies of learning through a single text. This may be due to several contributing factors, such as increased spacing between encounters and greater contextual diversity of individual exposures (K. Nation, ). The stimuli in this study were highly contextually constrained within the stories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies of L2 learning have found higher levels of vocabulary acquisition from more extensive reading (M. Horst, ; Webb & Chang, ) than usually reported in studies of learning through a single text. This may be due to several contributing factors, such as increased spacing between encounters and greater contextual diversity of individual exposures (K. Nation, ). The stimuli in this study were highly contextually constrained within the stories.…”
Section: Discussionmentioning
confidence: 99%
“…For example, within a single text there are smaller intervals between individual exposures whereas multiple texts give more spaced encounters that may be more beneficial for learning (Webb & Chang, ). Additionally, words read in multiple texts are likely encountered in more diverse contexts (K. Nation, ), which may enable readers to build more stable representations of the meanings of words. Conversely, children learn vocabulary better from being repeatedly read the same storybook than from the same number of exposures across different storybook contexts (J. Horst, Parsons, & Bryan, ).…”
Section: Incidental L1 Vocabulary Acquisition From Readingmentioning
confidence: 99%
“…The finding that reading ability is the driver of print exposure does not, of course, imply that exposure to print and thus exposure to orthographic forms is irrelevant to learning to read. To become a skilled reader, it is undoubtedly important to develop detailed lexical representations of words (Nation, 2017;Perfetti, 2007). However, while this may take as little as a single exposure in some readers (Tamura, Castles, & Nation, 2017), in poor readers, it takes much longer to consolidate new learning (Share & Shalev, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Stanovich proposed that this broadening skill gap is perpetuated by differences in literacy exposure: children with good language skills enjoy reading more, engage in more literacy activities and encounter more new words in doing so. Indeed, comprehension skill and reading experience have been shown to predict vocabulary growth (Cain & Oakhill, ), and are argued to be fundamental to literacy development (Nation, ). From this perspective, accelerated rates in vocabulary acquisition for children with good vocabulary skills are due to their increasing engagement with texts.…”
Section: Introductionmentioning
confidence: 99%